INNOVATIVE IMAGE STRATEGIES FOR DEVELOPING THE YOUTH SEGMENT OF INTERNATIONAL TOURISM (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The youth segment of the international tourism market is becoming increasingly important for both the tourism industry and the global economy as a whole. Modern socio-cultural changes taking place around the world under the influence of globalization and technological innovations make it one of the most dynamic and promising areas of development of the industry. Young tourists are not only becoming more and more active participants in the tourism market, they are significantly changing it, creating a whole culture of youth travel, which extends to other age segments.The purpose of the article. The purpose of the article is: based on the generalization of various approaches, to determine the features of the youth segment of international tourism, key factors influencing its development in modern conditions and to propose the main image strategies for forming an attractive brand of tourist destinations for young people.Methods. To achieve the goal, a holistic methodological toolkit was used, in particular: abstract-logical method, monographic, economic-statistical, graphic, as well as methods of a systemic approach, grouping and generalization.Results. The article explores various approaches to defining the boundaries of the youth segment, which is the basis for analyzing its specifics and place in international tourist flows. The types and features of youth tourism are considered, as well as its impact on the development of the global tourism industry. The focus is on the role of international organizations in supporting youth tourism and achieving strategic goals in this area. The impact of the COVID-19 pandemic on international tourist flows is analyzed, the dynamics of the main indicators characterizing the youth tourism market over the past decade are determined. In the context of modern challenges facing the youth tourism segment, the need to create a positive destination brand in the context of the needs and characteristics of the youth audience is substantiated, and the main image strategies necessary for this are proposed. The article emphasizes the importance of an innovative approach to their development, including the widespread use of digital technologies.Conclusions. The youth segment of the international tourism services market plays an increasingly important role in the development of the tourism industry and the world economy. Young tourists are distinguished by special characteristics: openness to new experiences, risk-taking, activity and greater integration with local communities, active use of digital technologies. Youth tourism largely determines the directions of the modern transformation of the tourism industry. Strategies for the development of youth tourism should be aimed at creating a bright and attractive image of a tourism brand for young people, which will arouse their interest and encourage them to travel.
Keywords: brand, image, emotional marketing, image strategy, innovation, youth segment of tourism, international tourism, tourism marketing.